Slope Earthquake Stability - Changwei, Yang; Jingyu, Zhang; Jing, Lian; Wenying, Yu; Jianjing, Zhang (Springer Nature Singapore : Imprint: Springer, 2017)
This book begins with the dynamic characteristics of the covering layerbedrock type slope, containing monitoring data of the seismic array, shaking table tests, numerical analysis and theoretical derivation. Then it focuses on the landslide mechanism and assessment method. It also proposes a model that assessing the hazard area based on the field investigations. Many questions, exercises and solutions are given. Researchers and engineers in the field of Geotechnical Engineering and Anti-seismic Engineering can benefit from it.